Effect of tuber size, storage temperature and storage duration on sprout growth in seed potatoes (Solanum tuberosum) - EZEKIEL, R; SINGH, BRAJESH (The Indian Journal of Agricultural Sciences, 2013)
The influence of tuber weight and storage temperature on sprout growth of seed potatoes was studied during 1995-96 in 2 Indian varieties, ’Kufri Bahar’ and ’Kufri Lalima’ and a Duteh variety ’Desiree’ at Modipuram. The number of sprouts/tuber showed a positive exponential relationship with the tuber weight while the length of the longest sprout showed a negative exponential relationship with it. The relationship between Sprout weight and tuber weight was logarithmic. Low temperature (4Â°C) treatment for 5 or more months increused the sprout number/tubel and the practical significance of this effect for the north Indian plains is discussed. The number of sprouts developed on desprouting was more when the tubers were stored at 12Â°C prior to desprouting compared to 20oC. Irrespective of the variety. the length of the longest sprout showed a rectangular hyperbolic relationship with storage period and a linear relationship with accumulated daydegrees above 4Â°C when stored at 12Â°C. But at 20oC, this relationship varied with the variety. The weight loss due to respiration and evaporation was more at 20Â°C than at 12Â°C and the weight loss/unit Sproul weight was higher in ’Kufri Lalima’.